Cryptocurrency and digital future in market relations - Tokatov, R.А.; Myrzaliyeva, Zh.T. (KSU Publ., 2018)
The article is devoted to cryptocurrency, which is one of the most important and practical problems today. According to researches of the authors in order to be in an equal position among the world's economic monopoly tendencies in tendency of the complex world globalization in the modern world cryptocurrency relation as an alternative method being as one of the most unique ways to overcome financial dependence is considering. Payment by the cryptocurrency today is the trend. The number of supporters of the new currency system increases with each passing day. Naturally, the demand for is forming in capitalist society. However, since there is no single cryptocurrency control mechanism, it is difficult to have confidence. It is not provided and the individual control of cryptocurrency by separate countries. According to some experts cryptocurrency may be a great driver to assign huge amounts of cash. If each state will be able to present the declaration to control legally or improve other ways of regulation, the cryptocurrency can replace the current financial system. And then the demand for it will increase. In comparison with Eastern Europe, cryptocurrency turnover in the Republic of Kazakhstan officially not forbidden, therefore the association requires the adoption of the law and it is the most urgent question in this sphere. Authors in order to resolve these problems exploring the world practice in relations of cryptocurrency, suggesting the contribution that it will be introduced in the domestic market, submit their views.
Нарықтық қатынастардағы криптовалюта жəне цифрлық болашақ
Криптовалюта и цифровое будущее в рыночных отношениях
Keywords: cryptocurrency; market relation; stock exchange; competition; bitcoin; issue; currency; electronic money; Gold fund; demand; digital transaction